Expressions of hope and aspiration among young people receiving rehabilitation services in Kampala, Uganda - Sabancı, Tümel (2015)
This study explores expressions of hope and aspiration among young people receiving rehabilitation services in Kampala, Uganda. The study objectives were (i) to examine expressions of hope and aspiration among young people receiving rehabilitation services (ii) to document the social determinants of hope and aspiration among young people receiving rehabilitation services and (iii) to assess barriers to the realization of hope and aspiration among young people receiving rehabilitation services. The study was carried out in Masooli Rehabilitation Centre of Ugandan Youth Development Link (UYDEL). UYDEL is a non- profit making organization (NGO) that was founded by a group of social welfare professionals in 1993. UYDEL currently runs four main programs concerning (i) child rights protection (child sexual abuse, child trafficking, commercial sexual exploitation, and child labour), (ii) HIV prevention among high risk groups of children and youth, (iii) alcohol and substance abuse, and (iv) adolescent sexual and reproductive health. In addition to the four major programs, UYDEL provides rehabilitation and livelihood skills training to young people and also conducts social research. This study took place with the participants from UYDEL receiving different vocational skills training. Young people in the rehabilitation centre were receiving mainly vocational trainings and learning different skills such as hair dressing, catering, construction, plumping, electronics and mechanics. Qualitative research methods and procedures such as purposive sampling of participants, in-depth interviews with the participants, and verbatim transcription of the collected data were used during the study. In-depth interviews were, for example, conducted with the young people receiving rehabilitation services in order to explore expressions of hope and aspiration. In-depth interviews were also conducted with the key informants (social workers of the centre). Data were analysed using the method of thematic analysis. Participants were chosen between the survivors of child trafficking and former street children. The study findings indicate that young people receiving rehabilitation services expressed hope and aspiration towards a better future in various ways which were (i) seeking ownership of highly valued possessions, (ii) exhibiting positive conduct and (iii) belief in supernatural interventions. The social determinants of the expressed hope and aspiration among young people receiving rehabilitation services were (i) receiving rehabilitation services, (ii) the availability of employment opportunities, and (iii) the provision of guidance and emotional support. Young people receiving rehabilitation services also experienced various barriers, which undermined realisation of their hope and aspiration. The major barriers according to the participants were (i) financial obstacles (ii) the risk for secondary abuse, and (iii) the familial challenges and resettlement. The study findings suggest various implications, for instance, for the Masooli Rehabilitation Centre, the Government of Uganda, and research. For example, finding ways for how to guide children to the education system who would like to continue their education is one of the implications for young people in the rehabilitation centre. This challenge can also be solved by developing more NGO links with education related NGOs in Kampala and finding donors for supporting young people’s education. Also, more links can be developed by the Masooli Rehabilitation Centre with different kinds of companies in order to provide more resources for the discharged young people.